Treasures of the world economic theory (Journal of Economic Research & Business Administration, 2016)
The article deals with the theory of economic dynamics which are put forward in work of the outstanding scientist – the economist, the classical KeynesianismRoy Forbes Harrod (1900-1978). The urgency and necessity of the logical culmination of the economic theory of the dynamics of R. Harrod justified in his work “Towards a Dynamic Economics” published in 1948.The authors of article attempted for the first time in the state language to show great importance of R. Harrod’s labor in the development of eco-nomic science led him to the global popularity as a leader Keynesian and the founder of the neo-Keynesian theory of the dynamics.
Keywords: Keynesian; economic theory; political economy; neoclas-sical theory; capital